(NiSTORIQ ZARUBEVNOJ MUZYKI(B.(Nhh WEK (B:(NhRESTOMATIQs (NNOTYs ((NmOSKWAs (NnAU^NO(B-(NIZDATEL_SKIJ CENTR mOSKOWSKAQ KONSERWATORIQs, 2010)
(NhRESTOMATIQ QWLQ@TSQ PRILOVENIEM K ODNOMENNOMU U^EBNOMU POSOBI@(B.s